Value for Money Assessment for Government and Business Entity Cooperation Projects by Using the Availability Payment Model: Proposition Methodology - Wibowo, Andreas (PT Penjaminan Infrastruktur Indonesia (Persero), 2019)
This paper proposes a quantitative methodology for ex-ante value-for-money (VfM) assessment to select the best modality option between conventional procurement and public-private partnership under the availability payment model for infrastructure provision within the Indonesian context. The proposed methodology incorporates efficient risk allocation principles into assessment to monetize risk retained by the government and risk transferred to the private sponsor. A simple numerical example under different scenarios of risk allocation for a road maintenance project case is presented to demonstrate its applicability. This paper also identifies some relevant issues, acknowledges limitations of the proposed methodology, and recommends directions for future research efforts.